Molecular and morphological evidence for short range endemism in the Kinnecaris solitaria complex (Copepoda: Parastenocarididae), with descriptions of seven new species - Karanovic, Tomislav; Cooper, Steven J.b. (Zootaxa, 2011)
Recent investigation of one of the larger calcretes in the uppermost reaches of the Carey palaeochannel in the Yilgarn region of Western Australia revealed an unprecedented diversity of copepod crustaceans. Twenty-two different species and subspecies, from six copepod families, represent 70% of the previously recorded copepod α-diversity in the whole region, although the area investigated is less than 3% of its surface. The aims of this study were to explore the diversity of the harpacticoid genus Kinnecaris Jakobi, 1972 using both molecular and morphological methods, establish precise species boundaries, find their accurate area of distribution, reconstruct phylogenetic relationships, and explore colonisation pathways. To achieve this we sampled very intensively in the area, as well as in two neighbouring palaeochannels, analysing more than 700 samples from 230 different localities, half of which contained copepods. Seven species are described here as new, five of them from the Yeelirrie palaeochannel (K. esbe sp. nov., K. lined sp. nov., K. linel sp. nov., K. linesae sp. nov., and K. uranusi sp. nov.) and one each from two neighbouring palaeochannels (K. barrambie sp. nov. and K. lakewayi sp. nov.). Parastenocaris jane Karanovic, 2006 from the Pilbara region, along with a newly described third Australian parastenocaridid genus from the Yilgarn, were used as outgroups in our molecular analysis. The COI fragment was successfully PCR-amplified from 12 parastenocaridid specimens using a nested combination of primers. All analyses supported the presence of at least seven genetically divergent lineages, most supported with very high bootstrap values. Three genera formed three separate clades, and the average pairwise distances between Kinnecaris morpho-taxa were found to be very high (8.2-16.8 %), while the highest divergences within morpho-taxa were 0.3%. Some conflict between molecular phylogenies and morphological data was observed when it came to recognizing different groups of species. While morphology indicates that K. esbe, K. linel, and K. uranusi represent a group of very closely related species, supported by a number of synapomorphies, molecular analyses suggest that K. linel and K. uranusi are only remotely related. We argue in favor of morphological data, until more markers can be studied to try to resolve these differences. In Yeelirrie, morphological evidence would suggest a downstream colonisation history in the genus Kinnecaris, where the most plesiomorphic form (K. linesae) lives in the uppermost reaches of the palaeochannel, and the trend in the caudal rami elongation and denser somite ornamentation is obvious downstream the palaeochannel (K. uranusi, K. linel, and then K. esbe), with the only exception being K. lined, which probably represents an independent colonisation event. Parastenocarids are copepods of freshwater origin, and we argure that they can probably disperse downstream during periods of increased rainfall, evolving into separate species in isolated calcrete pockets during periods of increased aridity. Although some of the questions remained unanswered in this study, detailed morphological and molecular observations indicate that we are not dealing with one widely distributed and variable species in the Yilgarn region, but rather with a complex of short range endemics. Areas of distribution for different species range from 30 km to less than 5 km in diameter. Very strong seasonal dynamics in this subterranean community was observed, and this is a novel concept for these ecosystems globally. A key to nine Australian species of Kinnecaris is also included.